Molecular characterization of chicken astrovirus and pathogenicity of a novel isolate in China - Han, Xiaofeng; Yin, Lijuan; Liang, Xiaoying; Liang, Huazhen (Frontiers in Microbiology, 2023)
As an enteric virus, chicken astrovirus has been related to various kinds of diseases in chickens, including white chick syndrome, runting-stunting syndrome, severe kidney disease, urate deposits and visceral gout, generating economic losses in the poultry industry globally. The complete ORF2 gene of 31 CAstV isolates in six provinces of China during 2020-2022 was characterized and analyzed with the purpose of better understanding the molecular epidemiology and genetic diversity of CAstV field isolates. Phylogenetic analysis which was based on the complete ORF2 (capsid) amino acid sequence of 31 CAstV isolates and 57 reference strains indicated that 2 isolates belonged to subgroup Ai, 10 isolates belonged to subgroup Bi, 3 isolates belonged to subgroup Bii, 5 isolates belonged to subgroup Biii, 7 isolates belonged to subgroup Biv, 3 isolates belonged to subgroup Bv, and one isolate (JS202103) belonged to a new B subgroup. In addition, the novel CAstV strain JS202103 was successfully isolated in vitro, and its whole genome shared 76.9-94.3% identity with the 29 CAstV reference strains. JS202103 caused hatchability reduction, dead embryos, kidney disease and visceral gout in chicken embryos. Moreover, this is the also the initial study focusing on diverse CAstV strains including subgroups Biii, Biv and Bv circulate in China. The current work contributes to improving our understanding of CAstV isolates in China, and it will also provide references for developing efficient measures to control this virus.